Efficacy of Evaporative Cool Chamber in Pasighat Condition, Arunachal Pradesh, India - Piloo, Ngangbam; Vida, Eloni (International Journal of Bio-resource and Stress Management, 2014)
Effectiveness of low cost cool chamber -an on-farm rural oriented storage structure which operates on the principle of evaporative cooling developed at IARI, New Delhi was studied under Pasighat condition. Freshly harvested vegetables viz. brinjal, frenchbean, green chillies, coriander and tomatoes were subjected to storage in evaporative cool chamber and ambient condition. The average minimum and maximum temperatures during storage period at cool chamber were 20.4oC and 30.23oC respectively and relative humidity were 74% and 95%, respectively. The minimum and maximum temperatures during storage at room temperature condition were 26.1oC and 31.8oC respectively and relative humidity were 59% and 79% respectively. Results indicate that storage at cool chamber increases the shelf life of all the vegetables by considerably reducing the physiological loss in weight (PLW), retaining sensory quality like colour, texture and increases marketability. Cool chamber was suitable for storing brinjal for 9-15 days, beans and green chillies for 8-10 days, coriander for 3 days and tomatoes for 14-15 days as against 4-5 days for brinjal, beans and green chillies, 1 day for coriander and 7 days for tomatoes in room condition.